Helping patients make informed decisions. Two-year evaluation of the Gustave Roussy prostate cancer multidisciplinary clinic. (August 2018) - Patrikidou, Anna; Maroun, Pierre; Patard, Jean-Jacques; Baumert, Hervé; Albiges, Laurence; Massard, Christophe; Loriot, Yohann; Escudier, Bernard; Di Palma, Mario; Arfi-Rouche, Julia; Rocher, Laurence; Merabet, Zahira; et al.
Highlights: The initial treatment decision for newly diagnosed non-metastatic prostate cancer is complex. Specialist multidisciplinary consultations focus on shared decision-making. The Gustave Roussy PCMC rendered high patient satisfaction and promoted active participation. Information offered at the Gustave Roussy PCMC strongly influenced final treatment decisions. Abstract: Objectives: The initial treatment decision for newly diagnosed non-metastatic prostate cancer is complex. Multiple valid approaches exist, without a clear and absolute consensus for every clinical scenario, and therefore specialist opinions may vary. Multidisciplinary consultations focusing on shared decision-making aim to provide an apposite tool for the initial treatment decision. We have evaluated the first two years of activity of the Gustave Roussy Prostate Cancer Multidisciplinary Clinic (PCMC), dedicated to the initial decision-making for non-metastatic prostate cancer. Methods: PCMC consists of two consecutive specialist consultations with a urological surgeon and a radiation oncologist, followed by a dedicated Tumor Board discussion. A study questionnaire was addressed to all PCMC patients via postal mail. Medical notes and questionnaire responses of 195 eligible patients were analyzed. Results: The questionnaire response rate was 69% (134 patients). Complete satisfaction rate was high (114 of 118 responders, 97%). Patients were offered new treatment options in 55% of cases, and felt better informed in 98% (122 of 125 responders). The double consultation was considered useful (124 of 129 responders, 96%). Reported feeling of active participation was significantly elevated (117 of 131 responders, 89%), while 46% of patients (57 of 125) modified their decision on the management of their prostate cancer following their PCMC consultation. Conclusions: The experience of a multidisciplinary consultation in the initial management of non-metastatic prostate cancer renders high patient satisfaction, improves their appreciation of feeling better informed, promotes active participation and shared decision-making and strongly influences their final decision.